2015
DOI: 10.1007/s11356-015-5697-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of biochar-mediated alleviation of toxicity of trace elements in plants: a critical review

Abstract: Trace elements (TEs) contamination is one of the main abiotic stresses which limit plant growth and deteriorate the food quality by their entry into food chain. In recent, biochar (BC) soil amendment has been widely reported for the reduction of TE(s) uptake and toxicity in plants. This review summarizes the role of BC in enhancing TE(s) tolerance in plants. Under TE(s) stress, BC application increased plant growth, biomass, photosynthetic pigments, grain yield, and quality. The key mechanisms evoked are immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
109
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 421 publications
(116 citation statements)
references
References 158 publications
4
109
0
3
Order By: Relevance
“…Recently, a carbon-rich economically viable soil amendment like biochar (BC), produced by Communicated by: Elena Maestri pyrolyzing biowaste materials under limited oxygen supply, has attained significant interest to improve soil physical, chemical, and biological properties due to its high organic carbon content, surface area, cation exchange capacity, etc. (Almaroai et al 2014;Rizwan et al 2016c). Biochar is also widely used as a soil amendment to immobilize toxic metals and hence reduced their toxicity to plants when applied in contaminated soils (Houben et al 2013a;Houben et al 2013b;Almaroai et al 2014;Rizwan et al 2016cRizwan et al , 2016d.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a carbon-rich economically viable soil amendment like biochar (BC), produced by Communicated by: Elena Maestri pyrolyzing biowaste materials under limited oxygen supply, has attained significant interest to improve soil physical, chemical, and biological properties due to its high organic carbon content, surface area, cation exchange capacity, etc. (Almaroai et al 2014;Rizwan et al 2016c). Biochar is also widely used as a soil amendment to immobilize toxic metals and hence reduced their toxicity to plants when applied in contaminated soils (Houben et al 2013a;Houben et al 2013b;Almaroai et al 2014;Rizwan et al 2016cRizwan et al , 2016d.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is also widely used as a soil amendment to immobilize toxic metals and hence reduced their toxicity to plants when applied in contaminated soils (Houben et al 2013a;Houben et al 2013b;Almaroai et al 2014;Rizwan et al 2016cRizwan et al , 2016d. However, little information is available on the role of BC in reducing Ni toxicity in plants (Rizwan et al 2016c). Furthermore, it has been reported that gravel sludge (GS) application improved plant growth under metal stress (Iqbal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned by Rizwan et al (2016), there is a limited number of reports describing the effect of BC on the biochemical and physiological activities of plants. One of the important indicators of plant metabolism is composition and content of amino acids (AAs), which are affected by environmental conditions (Nikiforova et al 2006).…”
mentioning
confidence: 99%
“…O biocarvão surge como uma alternativa, pois têm como foco principal criar uma boa sintonia entre a fertilidade do solo, produção de alimentos, o sequestro de carbono, a redução dos gases do efeito estufa e redução da toxidez de elementos traços no solo. [4][5][6][7] Os teores de carbono no solo são relativamente baixos, mas é um dos responsáveis pela emissão dos gases do efeito estufa ao fluxo atmosférico (GEE). Assim, o potencial do biocarvão no sequestro de carbono no solo, evitando que ele seja liberado para a atmosfera, tem atraído grande atenção de pesquisadores.…”
Section: Introductionunclassified